PENGARUH PEMASARAN RELASIONAL DAN PROMOSI TERHADAP LOYALITAS NASABAH TABUNGAN SIMAS GOLD PADA PT. BANK SINARMAS, TBK CABANG MANADO - SAIYANG, RICHARD ANDRE ANDRE; AREROS, WILLIAM AGUSTINUS; PIO, JHONLY (Sam Ratulangi University, 2017)
ABSTRACThis research is based on thoughts on relationship marketing and promotion, especially the promotionof sales to customers loyalty to the Bank. With the growing efforts of the banking industry today, the level ofcompetition between banks is increasingly competitive, each bank has a strategy to give a sense of loyalty tothe customers to choose or save the money in bank. Because with the existence of relationship marketinginnovation is one of the supporting factors such as; Trust, Familiarity, and professional awareness tocustomers. Also, promotional factors are particularly encouraging sales promotions such as: attracting newbuyers, rewarding old customers, increasing purchasing power from old customers, avoiding customers fromswitching to other brands, popularizing brands/increasing brand loyalty , Increasing short-term sales volumein order to increase long-term market share. In order to increase the customers loyalty.This activity was held at Bank Sinarmas Manado branch in order to know the relation betweenrelationship marketing and promotion to customer loyalty of Simas Gold. Besides, this research is expected tobe input to the leadership of Bank Sinarmas Manado branch and is a contribution in increasing the loyalty ofeach customer.In this research using descriptive statistical analysis deductive and inductive statistics .. Datacollection using the instrument in the form of questionnaires/interviews, observation and document studies,and for data analysis using multiple regression statistics using SPSS 16. Population in the study are all SimasGold customers at PT. Bank Sinarmas, Tbk Manado, by taking samples of 82 respondents.The results of this study to answer the hypothesis that there is a relationship between relationalmarketing and promotion of customer loyalty, with a determinant indicates 8.4% which means that the increaseor decrease in customer loyalty depends on relational marketing and promotion, the remaining 91.6% of otherfactors. Based on the calculation of multiple linear regression analysis, it can be seen that the value of F hitungis greater than the value of F tabel (3.613> 3.11), x and the value of significance count (sig) = 0.032 is smallerthan the value Î± = 0.05. These results prove that simultaneously or together the relational marketing variables(X1), and promotional variables (X2) have an influence on customer loyalty Simas Gold at PT. Bank Sinarmas,Tbk Manado branch. The t-value of the relational marketing variable (X1) is smaller than the t-table value (-0.609 <1.668) and the significance value (sig.) Is greater than the required ((0.544> 0.05). These resultsindicate that the relational marketing variables do not influence predominantly to loyalty, so Ha is rejected, soH0 formulated as: relational marketing does not affect predominantly to loyalty, because the value ofsignificance is greater than ï¡ which is required with 95% confidence interval. Or 0.5. The value of t-count ofpromotion variable (X2), is greater than t-table value (2,646> 1,668) and its significance value (sig.) Is lessthan ï¡ required (0,010 <0,05). These results indicate that the promotion variable has a positive and dominantinfluence on customer loyalty Simas Gold saving at PT.Bank Sinarmas, Tbk branch Manado. This shows thatH0 is rejected, Ha accepted, so it is concluded that there is influence of promotion with customer loyalty simasgold saving. In this case also supported by the probability value of 0.010 <0.05. These results indicate thatpromotion variables dominantly affect loyalty, then H0 is rejected, so that Ha formulated as: promotiondominant influence on loyalty, because the value of significance is smaller than ï¡ required with 95%confidence interval. Or 0.5.Keywords : Relationship marketing, promotion, loyalty